Comparative clinical outcomes of dual cannulated screw-cable system vs. Kirschner wire-cable fixation in type C patellar fractures - Yang, Huan; Yuan, Yusong; Shi, Lei; Si, Fangda; Liu, Jiaqi; Chen, Ying; Xu, Xiaodong (Frontiers in Surgery, 2025)
IntroductionTo compare the clinical efficacy and safety of the dual cannulated screw-cable (DCSC) system with those of conventional Kirschner wire-cable (KWC) fixation in the management of patellar fractures. Traditional KWC fixation, while widely used since the 1970s, is associated with high complication rates, including symptomatic hardware irritation (up to 42%) and loss of reduction (12%–15% in transverse fractures), due to its biomechanical limitations such as lack of interfragmentary compression and prominent hardware causing soft tissue irritation. The DCSC system, introduced as a promising alternative, offers active interfragmentary compression and reduced soft tissue irritation, potentially addressing these limitations. However, few clinical studies have directly compared the outcomes of DCSC and KWC fixation in patellar fractures. This study aims to fill this gap by evaluating functional recovery, radiographic union, and complication rates between the two fixation methods.MethodsThis retrospective cohort study included 127 patients with patellar fractures (AO/OTA 34-C) treated between January 2020 and December 2023. The patients were stratified into DCSC (n = 26) and KWC (n = 101) groups. The primary outcomes included functional recovery (Lysholm and Böstman scores) at 3 and 12 months postoperatively. The secondary outcomes included radiographic union time, complication rates, and reoperation rates. Between-group comparisons were performed using t tests and chi-square tests (p < 0.05).ResultsThe DCSC group demonstrated superior short-term functional outcomes, with significantly higher Lysholm scores at 3 months (76.0 ± 6.1 vs. 70.4 ± 2.9, p < 0.001) and significantly higher Böstman scores across all fracture classifications (C1: 21.5 vs. 17.5; C2: 21.6 vs. 17.2; C3: 21.3 vs. 17.6; all p < 0.001). Notably, C2 fractures treated with DCSC exhibited the greatest improvement in Lysholm scores (at 3 months, p < 0.001). DCSC also resulted in shorter operative times (62.9 ± 1.8 vs. 76.0 ± 1.4 min, p < 0.001) and reduced symptomatic hardware irritation (3.8% vs. 21.8%, p = 0.03). Radiographic union was faster in the DCSC group (3.04 vs. 3.50 months, p < 0.001). However, the Lysholm and Böstman scores at 12 months were similar between the groups (p > 0.05), and the reoperation rates at 12 months were comparable (3.8% vs. 2.0%, p = 0.82).ConclusionCompared with KWC fixation, the DCSC system provides superior early functional recovery, fewer complications, and faster fracture healing, particularly in complex intra-articular fractures (OTA 34-C2). However, the benefits of the DCSC system in simpler or more comminuted fracture (C1/C3) diminish over time, and caution is warranted when using this system in comminuted or distal coronal plane fractures owing to potential compression limitations. These findings support the use of DCSC as a first-line option for C2 fractures, although long-term studies are needed to assess implant durability.